An appearance‐preserving simplification method for complex 3D building models. Issue 2 (5th February 2019) - She, Jiangfeng; Gu, Xiaoyan; Tan, Junzhong; Tong, Ming; Wang, Chaofan
Abstract: The simplification of 3D building models to effectively reduce model complexity and improve rendering efficiency is an important component of 3D GIS. To reduce the data volume while preserving the model appearance, this article proposes a novel simplification method for complex 3D building models. Texture discontinuities are addressed by developing a new data model that records the mapping relation between the texture coordinates of each vertex and its neighboring triangles. The surface mesh of the building model is then segmented into regions, guided by topology and appearance. Finally, the mesh segmentation information is used to derive an improved error metric that considers both geometric and texture errors, and the texture coordinates are adjusted after each simplification operation. A series of comparative experiments alongside traditional methods demonstrates that our approach achieves a good balance between geometric fidelity and texture preservation, and produces simplified 3D building models with better visual quality.